2021
DOI: 10.1097/ico.0000000000002748
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Keratoplasty and Corneal Eye Banking

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…There are conflicting reports about the presence and replication of the SARS-CoV-2 virus in the eye tissue with viral particles being detected in COVID-19-infected patients. However, others report no such viral presence in the post-mortem eye tissues of infected patients [ 17 ]. Miner et al reported that there is no significant risk of viral replication in the explant of the cornea and, hence, there are no significant risks associated with corneal transplantation [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There are conflicting reports about the presence and replication of the SARS-CoV-2 virus in the eye tissue with viral particles being detected in COVID-19-infected patients. However, others report no such viral presence in the post-mortem eye tissues of infected patients [ 17 ]. Miner et al reported that there is no significant risk of viral replication in the explant of the cornea and, hence, there are no significant risks associated with corneal transplantation [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, others report no such viral presence in the post-mortem eye tissues of infected patients [ 17 ]. Miner et al reported that there is no significant risk of viral replication in the explant of the cornea and, hence, there are no significant risks associated with corneal transplantation [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported a significant RT-PCR positivity rate of nasopharyngeal swabs obtained from presumed COVID-19-negative potential donors, ranging from 4.8% to as high as 18.64%. [ 1 15 16 ] Arora et al . [ 15 ] also reported a high viral load (Ct < 25) in 54.54% of the positive cases, suggestive of high risk of disease transmission to the health personnel handling the tissue.…”
Section: Routine Donor Testing: Weighing the Pros And Consmentioning
confidence: 99%
“…Elective health care services have temporarily taken a backseat, and eye-banking and keratoplasty services have come to a near-standstill. [ 1 ] As we learn to live with the pandemic and move forward, there is a need to revise existing norms and guidelines in order to optimize eye-banking services and effectively tackle the growing backlog of routine keratoplasty procedures.…”
mentioning
confidence: 99%